The Views of Turkish Immigrants on Multicultural Policies in Australia: The Impact of Migration Duration - Ayşe Mahinur Tezcan (Medya ve Kültür)
There have been discussions on cultural diversity occurring through migrations and on interrelationships among different cultures. In this context, various multiculturalism policies aim to ensure intercultural harmony in different ways. The paper covers the multicultural policies in Australia, which is one of the countries where multicultural policies are implemented, and the perceptions of Turkish immigrants living in Australia on the policies. The study is supported by literature review as well as field research. In the literature review section Australia’s multicultural policies are historically examined. In the field research section, the results of the survey conducted on 152 Turkish immigrants living in Sydney will be discussed.*** It is concluded that Turkish immigrants consider multicultural policies are implemented compulsorily, not willingly. Besides, the general view of our participants is that Australian people will never consider Turkish immigrants as real citizens. Turkish immigrants in Sydney think that they will always remain in the immigrant status.